CJD, ACD, JB, and a one-in-million find: Reflections on a scholarly journey with the creator and inspiration of Sherlock Holmes - Heseltine, Alexa (My University, 2025)
As I end my undergraduate collegiate career and begin to plan my next chapter, I think about the role that Sherlock Holmes has played on the last four years of my life. When I began my time at Kansas State University in the Fall of 2021, I was enrolled as a Medical Microbiology major on the Pre-Med track. Unbeknownst to me, I was about to be introduced into the world of public health, where the likes of Samuel Crumbine, Joseph Bell, and John Shaw Billings were waiting for me to unearth their stories. Growing up, I had somewhat of an interest in medicine and most definitely an interest in science, so when it came to deciding a major, Medical Microbiology felt right, but I was not exactly sure why. As a freshman in college, I hit the ground running enrolling myself into the “Hacking the MCAT” CAT Community; Public & Veterinary Health in the Age of Sherlock Holmes; and Phage Hunters with the intent to foster a degree that would ultimately lead to medical school. These three courses independently and collectively paved the way for what would become four years of intellectual curiosity combined with a consistent confusion surrounding what career pathway I should be on.